Cyclophilins as Modulators of Viral Replication - Stephen D. Frausto; Emily Lee; Hengli Tang (Viruses, 2013)
Cyclophilins are peptidyl‐prolyl cis/trans isomerases important in the proper folding of certain proteins. Mounting evidence supports varied roles of cyclophilins, either positive or negative, in the life cycles of diverse viruses, but the nature and mechanisms of these roles are yet to be defined. The potential for cyclophilins to serve as a drug target for antiviral therapy is evidenced by the success of non-immunosuppressive cyclophilin inhibitors (CPIs), including Alisporivir, in clinical trials targeting hepatitis C virus infection. In addition, as cyclophilins are implicated in the predisposition to, or severity of, various diseases, the ability to specifically and effectively modulate their function will prove increasingly useful for disease intervention. In this review, we will summarize the evidence of cyclophilins as key mediators of viral infection and prospective drug targets.